العلاقة بين حجم صناديق الاستثمار وعوائدها نموذج التجربة المصرية - بوحسون, ياسر; زهرة, شادي (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يتناول هذا البحث بالدراسة والتحليل العلاقة بين حجم صناديق الاستثمار وعوائدها السنوية ، حيث يدرس البحث التجربة المصرية كمثال للعلاقة السابقة. بداية يتناول الباحث مفهوم الاستثمار وكيفية حساب عوائده، والتي يستفيد منها في حساب معدل العائد السنوي لصندوق الاستثمار، ثم يأخذ الباحث عينة مختارة من صناديق الاستثمار العاملة في مصر، بهدف تحليل العلاقة بين العائد السنوي لهذه الصناديق وأحجامها. في النهاية يتناول الباحث قانون سوق الأوراق المالية في سوريا، بهدف تقييم بعض المواد الخاصة بصناديق الاستثمار، أخيراً يخلص البحث إلى مجموعة من النتائج والاقتراحات. The research studies and analyzes the relation between investment funds' size and their annual returns, this research studies the Egyptian experiment, as an example of the past relation. First, the researcher studies the concept of investment, and how we can calculate its returns, which we use when we calculate the annual returns of investment funds, and then the researcher chooses a selected pattern of Egyptian investment funds trying to analyze the relation between annual returns of these funds and their size. At the end, the researcher studies and analyzes the law of securities market in Syria to evaluate some investment funds' units, and finally, this research ends to some results and suggestions.